2012
DOI: 10.3390/cryst2041393
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Random Nonlinear Photonic Crystals Based on Strontium Tetraborate

Abstract: Properties of strontium tetraborate (SBO) and features of as-grown anti-parallel domains are summarized. From the point of view of nonlinear optics, these domains form nonlinear photonic crystals (NPC). Applications of NPC to the deep ultraviolet generation and fs pulse diagnostics are described. NPC and SBO are prospective media for the creation of a widely tunable source of fs pulses in the vacuum ultraviolet and for autocorrelation diagnostics of broadly tunable sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Twinned structures of SBO crystals were reported by Aleksandrovsky et al, for the first time. 20,21 They succeeded in growing partially twinned SBO crystals by the Czochralski method (CZ method). To control the formation of twin boundaries, the incorporation of defects is further required, which can be achieved by the periodic application of an electric field during the growth under a high-temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Twinned structures of SBO crystals were reported by Aleksandrovsky et al, for the first time. 20,21 They succeeded in growing partially twinned SBO crystals by the Czochralski method (CZ method). To control the formation of twin boundaries, the incorporation of defects is further required, which can be achieved by the periodic application of an electric field during the growth under a high-temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most attractive features of borate crystals such key characteristics as their transparency in deep UV range, high optical damage threshold combined with appropriate nonlinearity, and suitable chemical stability of optical surface should be pointed, and they define wide applications of borate materials in modern laser optics and nanophotonics [1][2][3][4][5][6][7][8][9][10][11]. Within borate matrices, boron ions can be either three-or four-fold coordinated, and the combination of BO4 and BO3 units produces large variety of crystal structures with differing properties [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, since borates are non-ferroelectric crystals, with the utilization of the poling method and the hot-pressing method it is difficult to control twin boundary orientation. Aleksandrovsky et al, for the first time, reported twinned structures of SBO crystals [17,18]. They succeeded in growing partially twinned SBO crystals by the Czochralski method (CZ).…”
Section: Introductionmentioning
confidence: 99%